Parcerias público-privadas no Brasil: em busca de eficiência por meio de alocação de riscos - Franco, Viviane Gil (2007)
Risk allocation is one of the main sources of efficiency gains in public-private partnerships projects (PPP). Resting on this evidence, this dissertation has as a main goal to assess and analyse the risk allocation in PPP projects in Brazil. To reach this purpose it is used the case study of the MG-050 Highway PPP project contract. The contract analysis seeks to identify the risk allocation strategy intended by the Minas Gerais government and to make a comparision between this strategy and the international practices and principles. This analisys takes in count too the brazilian federal PPP Law (Law 11.079/2004) which delineates the brazilian partnerships model. From the case study, it s possible to identify an effort to apply the main risk allocation principles to the contract. However, there are some critical points that could create difficulties to the contract performance